GC-MS profiling and molecular docking of bioactive compounds from Strychnos lucida on reproductive protein targets - ST. AISYAH SIJID; HERRY SONJAYA; RATMAWATI MALAKA; HASBI HASBI (Society for Indonesian Biodiversity, 2025)
Abstract. Sijid SA, Sonjaya H, Malaka R, Hasbi H. 2025. GC-MS profiling and molecular docking of bioactive compounds from Strychnos lucida on reproductive protein targets. Biodiversitas 26: 3469-3484. Strychnos lucida, locally known as Kayu Ular (KU), is traditionally used in various regions of Indonesia, commonly used to enhance stamina and vitality, with anecdotal claims suggesting benefits related to reproductive function. This study aimed to evaluate the plant’s potential in reproductive health through phytochemical screening, Fourier Transform Infrared Spectroscopy (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS), and molecular docking analysis. The extract was obtained by macerating the plant material in 96% ethanol. Phytochemical screening confirmed the presence of flavonoids, alkaloids, tannins, and saponins, which are associated with antioxidant, anti-inflammatory, and hormonal modulatory activities. Among them, flavonoids and saponins are particularly known to improve fertility enhancement and hormonal balance. A total of 66 compounds were identified by GC-MS, with Lunacrine (52.71%) as the most abundant. Molecular docking was conducted on four dominant compounds—Lunacrine, (Z)-11-octadecenoic acid, hexadecanoic acid, and (9Z,12Z)-octadeca-9,12-dienoic acid—against five reproductive-related protein targets: AMPK, SIRT1, COX-2, PPAR-?, and Dynein. Lunacrine exhibited strong binding affinities with the target receptors AMPK (-7.8 kcal/mol), SIRT1 (-8.5 kcal/mol), and COX-2 (-8.9 kcal/mol), suggesting its potential to modulate energy metabolism, oxidative stress, and inflammation—critical processes in hormonal regulation and reproductive function. These findings support the traditional use of S. lucida for reproductive health and highlight Lunacrine as a promising candidate for further phytopharmaceutical development. Follow-up in vitro and in vivo studies are recommended to validate its therapeutic potential.